THE EFFECT OF USING SULFUR SOAP ON THE EFFECTIVENESS OF HANDLING DEMODICOSIS CASES IN KINTAMANI CROSS-BREED DOG - Sarungallo, Yoga Pratama Mambela; Suartha, I Nyoman; Widyastuti, Sri Kayati (Buletin Veteriner Udayana, 2024)
Demodecosis is a skin disease caused by Demodex spp. mites that can cause itching and trigger the scratching reflex. The purpose of writing this case report article is to determine the cause of the skin disease that occurred in the case dog and the effectiveness of the sulfur soap treatment performed. A male Peranakan kintamani dog named Siba, 5 months old, weighing 7 kg, and having black hair color had skin problems since 1 month before. The dog's appetite was good, defecation and urination were normal. The dog was fed rice mixed with chicken. The case dog was kept loose and sometimes tied around the house. The results of the physical examination showed skin lesions in the form of erythema, crusts, alopecia, and hyperkeratosis on the face, neck, front legs, hind legs, abdomen, around the anus and swollen interdigit. A deep skin scrapping examination found Demodex spp. Routine hematology examination showed the case dog was anemic. The dog was diagnosed with demodecosis. Treatment was ivermectin, antihistamine (diphenhydramine), vitamin B complex, and sulfur soap. Evaluation after 14 days showed changes in the lesions and reduced pruritus. It is recommended to implement good husbandry management and maintain the dog's immunity to avoid recurrent infections.